ANALISIS EKONOMI HUTAN MANGROVE DI TELUK KOTANIA KABUPATEN SERAM BAGIAN BARAT - Lutfia I. Litiloly; Gun Mardiatmoko; Debby V. Pattimahu (JURNAL HUTAN PULAU-PULAU KECIL, 2020)
Analysis of the economic value of mangrove forests in Kotania Bay, West Seram District is important to study. Mangrove forest ecosystems are often regarded as public property resources that can be used by anyone without regard to its sustainability aspects. Over-utilization results in the depletion of mangrove forest resources and the ability of ecosystems to provide environmental services is decreasing. The low knowledge of the local community for the potential of mangrove forests as an economic source, it is necessary to do an economic valuation of the magnitude and benefits of mangrove forests. The Methods used in this study is Total Economic Value (TEV) based on direct benefits, indirect benefits and the optional benefits. The results showed that the direct benefits of economic value is IDR 318,360,000 / year (44%), indirect benefits is IDR 243,468,473 / year (34%), optional benefits is IDR 163586,356 / year (22%) while the TEV is IDR 725,414,829 / year.